Implementation of Augmented Reality 3D Catalog And 2D Motion Based on Multimarker - Santoso, Riki Adi; Cahyono, Nuri (Universitas Negeri Padang, 2024)
In the current era of technological progress, various kind of technology can be applied in multiple fields. One technology that is currently popular is Augmented Reality (AR). This technology can be used in several ways, for example, AR for the learning proccess, AR for simulations and AR for promoting a product. This research used Multimarker-based Augmented Reality technology to promote products at Essential Bakery. Essential Bakery is an MSME that operates in the food sector, one of which is bread. The research aims to help MSME Essential Bakery promote its product to make the services provided more attractive and innovative. This research uses the MDLC (Multimedia Development Life Cycle) research method. This Augmented Reality Uses Multimarker-based tracking, which is a differentiator in previsious research. Hopefully, this research will improve effective and innovative services by usong Augmented Reality as a promotional medium. It is hoped that human resources in indonesia will be more aware of the latest technology currently available. The result of this research is that the application can run 3D objects and 2D motion through the markers that have been created.